Assessment of Private Paravets Practices towards Veterinary Extension Services in Nepal - Thapa, Narbikram (Journal of Training and Development, 2020)
The study aims to assess the performance of paravets towards veterinary extension services in Nepal. The participatory methods like questionnaire survey, key informant interview, focus group discussion, direct field observation, force field analysis and score ranking was adopted during the study. The quality of the Private Paravets was sound in terms of relevance, appropriateness, targeting, and sustainability issues. Project activities associated with Private Paravets promotion were observed appropriate and in line with the needs of farmers. The concerned private paravets were found to be working effectively for institutional, social and economic transformation of the beneficiaries. Large majority of the Paravets have been providing veterinary service on technical advice, curative services (98 %), AI (87 %) and vaccination (75%) against hemorrhagic septicaemia and black quarter diseases in the cattle and buffaloes. There has been increased access to veterinary extension services in the rural farming communities because of increased accessibility to Paravets. In the study areas 89 %paravets have annual turnover of Rs less than 2 lacsto3-5lacs in their fee based private veterinary services. Overwhelming majority of the Paravets had future plan to expand their business. Of the total 96 % Paravets expressed job satisfaction for their current veterinary private practices despite some problems. The private paravets seems to be instrumental and sustainable to provide services towards veterinary and livestock production technology in the study areas. However, there is room for improvements to make it economically viable, technically sound, legally regulated and developing professional ethics as Paravets practices in Nepal.